TAFE workers’ experiences of neoliberal reform in the Australian VET sector, 2012-2017 - Rodd, Piper (New Zealand Sociology, 2021)
This article examines neoliberal reforms of the vocational education and training (VET) sector in Australia. It focuses on the case study of the state of Victoria, which underwent a period of significant reform between 2012 and 2017. The article documents the significant policy reforms which negatively impacted on Australia’s VET sector, drawing on media and academic commentary to illustrate the public and personal ramifications of these reforms, and arguing that while these reforms were well-documented at the time, the voices of those most immediately affected were largely silenced by both the speed of these changes and the ideology underpinning them. This article uses interview data to provide unique insight into the direct experiences of stakeholders who worked in senior management and teaching roles in the Australian VET sector during this period. Their voices are used to critique policies adopted by bipartisan governments at both state and federal levels as they relate to the marketisation and commodification of VET.